2011
DOI: 10.1124/mol.110.068296
|View full text |Cite
|
Sign up to set email alerts
|

Coupling to Polymeric Scaffolds Stabilizes Biofunctional Peptides for Intracellular Applications

Abstract: Here, we demonstrate that coupling to N-hydroxypropyl methacrylamide (HPMA) copolymer greatly enhances the activity of apoptosis-inducing peptides inside cells. Peptides corresponding to the BH3 domain of Bid were coupled to a thioesteractivated HPMA (28.5 kDa) via native chemical ligation in a simple one-pot synthesis. Peptides and polymer conjugates were introduced into cells either by electroporation or by conjugation to the cell-penetrating peptide nona-arginine. The molecular basis of the increased activi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
19
0
4

Year Published

2013
2013
2015
2015

Publication Types

Select...
6

Relationship

6
0

Authors

Journals

citations
Cited by 16 publications
(26 citation statements)
references
References 44 publications
2
19
0
4
Order By: Relevance
“…We have previously shown that electroporation affords efficient import and homogenous cytoplasmic distribution of conjugates and free peptides. [21] Prior to testing the effect of the HPMA-SLP228 conjugate on protein microcluster formation, we determined the average intracellular concentrations of the conjugates achieved by electroporation, by using constructs with fluorescent labels (Figure S1 B). Cells were analyzed with a combination of intracellular fluorescence correlation spectroscopy (FCS) and avalanche photodiode (APD) imaging.…”
Section: Resultsmentioning
confidence: 99%
“…We have previously shown that electroporation affords efficient import and homogenous cytoplasmic distribution of conjugates and free peptides. [21] Prior to testing the effect of the HPMA-SLP228 conjugate on protein microcluster formation, we determined the average intracellular concentrations of the conjugates achieved by electroporation, by using constructs with fluorescent labels (Figure S1 B). Cells were analyzed with a combination of intracellular fluorescence correlation spectroscopy (FCS) and avalanche photodiode (APD) imaging.…”
Section: Resultsmentioning
confidence: 99%
“…Zuschriften zuvor beobachtet, [14] verlässt Fluorescein die Zellen in weniger als einer Stunde. Im Gegensatz dazu zeigen sowohl PEGylierte als auch unPEGylierte BH3-Peptide eine homogene Verteilung während der ersten 5 h und auch nach 6.5 h war die Fluoreszenz überwiegend homogen verteilt (Abbildung 3).…”
Section: Methodsunclassified
“…In einer früheren Studie haben wir ein HPMAgekoppeltes BH3-Peptid untersucht und beobachtet, dass ein Anstieg der proteolytischen Stabilität nicht von einer verlängerten intrazellulären Residenzzeit begleitet wurde. [14] Da wir diese Korrelation jedoch für mehrere andere Peptide nachweisen konnten, zeigt unsere Beobachtung im vorliegenden Experiment, dass das unPEGylierte BH3-Peptid ein proteolytisches Fragment bildet, das nicht direkt die Plasmamembran überwinden kann. [25] Daraufhin untersuchten wir den Einfluss der stabilisierenden PEG-Phosphoramidatmodifikation auf die intrazelluläre Aktivität der BH3-Peptide.…”
Section: Methodsunclassified
See 2 more Smart Citations